Capacidade de mascaramento de diferentes combinações de resina composta após envelhecimento em água - Perez, Bibiana Gabardo (2017)
ADVISOR: Letícia Brandão Durand The aim of this study was to evaluate the effectiveness of the layering technique of three resin composite restorative systems (IPS Empress Direct, Charisma Diamond and Filtek Z350XT) on masking a discolored background (C4) after a period of 1 year of aging in deionized water. Ninety 1.5 mm-thick specimens were made from three different restorative systems. The specimens were divided into groups and sub-groups according to the restorative system used and resin composite shade combi-nation used in the layering technique (enamel, body and dentin). The color meas-urements of the specimens were performed on the C4 substrate at two times: after a 24-hour immersion period in deionized water (T0) and after 1 year of aging (T1), through a reflection spectrophotometer (SP60, EX-Rite). The masking ability was evaluated from the calculation of ΔE, performed between the inherent background and the C4 background, at baseline and after water aging Comparative analyses were performed between the color measurements on the C4 background at the two times from CIELAB and CIEDE2000 formulae. ANOVA and Turkey's post hoc test (a=0.05) were performed to analyze the ΔEab and ΔE00 mean values. Only the sub-groups of the restorative system IPS Empress Direct 0.5mm enamel + 1.0mm dentin and 1.5mm dentin did not differ statistically between times, both for CIELAB and for CIEDE2000. None of the subgroups analyzed presented clinically acceptable values after aging.